Effect of standardized Aronia Melanocarpa extract on oxidative stress and antioxidant status in patient with cronic myeloid leukemia treated with imatinib - Bojan Labachevski; Dragica Zendelovska; Marija Petrushevska; Marija Popova-Labachevska; Aleksandra Pivkova-Veljanovska; Liljana Gjatovska-Labachevska; Nevenka Ridova; Sanja Trajkova; Irina Panovska-Stavridis; Trajan Balkanov (Makedonsko Farmacevtski Bilten)
Antioxidant status in patients with chronic myeloid leukemia (CML) is significantly decreased in comparison with healthy individuals. Oxidative stress (OS) may be associated with the pathophysiology of CML and can influence on development of resistance to imatinib. The aim of our study was to investigate the effect of Aronia melanocarpa extract (A-lixir 400 PROTECT®) on OS in CML patients treated with imatinib. In this study a total of 40 CML patients treated with imatinib for longer than 1 month were included: twenty patients were treated with imatinib and A-Lixir 400 PROTECT® (treatment group) and twenty patients were treated only with imatinib (control group). OS parameters (d-ROM, PAT and OSI) were measured at the initial visit, and after 21 and 42 days of treatment. Adjuvant treatment with A-Lixir 400 PROTECT® could lead to attenuation of OS. d-ROM and OSI in this group of patients were significantly higher at initial visit when compared to values after 21 and 42 days of treatment (p<0.05). Total antioxidant capacity (PAT) was significantly higher after 21 and 42 days of treatment initiation in comparison with the pretreatment values. In the control group no significant differences were obtained between investigated parameters at any time of measurement. We can conclude that adjuvant treatment with A-Lixir 400 PROTECT® after 21 and 42 days lead to significant reduction of OS in patients with CML treated with imatinib.